2006
DOI: 10.1210/jc.2006-0980
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adipokines and Cytokines in Gestational Diabetes and Macrosomia

Abstract: GDM is linked to the down-regulation of adiponectin along with Th1 cytokines and up-regulation of leptin and inflammatory cytokines. Macrosomia was associated with the up-regulation of Th1 cytokines and the down-regulation of the obesity-related agents (IL-6 and TNF-alpha, leptin, and adiponectin).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
309
2
20

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(363 citation statements)
references
References 54 publications
29
309
2
20
Order By: Relevance
“…Despite the presence of insulin resistance in diabetic rats, our results showed no differences between groups at the times analyzed regarding plasma TNF-α levels. Studies of diabetic pregnant women have shown an increase in serum levels of TNF-α compared to healthy pregnant women (9)(10)(11)(12). Thus, our results do not agree with the literature data for women but do show that TNF-α is not a good predictor of insulin resistance or maternal-fetal changes in this model of diabetic rat pregnancy.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Despite the presence of insulin resistance in diabetic rats, our results showed no differences between groups at the times analyzed regarding plasma TNF-α levels. Studies of diabetic pregnant women have shown an increase in serum levels of TNF-α compared to healthy pregnant women (9)(10)(11)(12). Thus, our results do not agree with the literature data for women but do show that TNF-α is not a good predictor of insulin resistance or maternal-fetal changes in this model of diabetic rat pregnancy.…”
Section: Discussioncontrasting
confidence: 97%
“…The decrease in IL-10 concentration in term pregnancies is consistent with the results obtained by Kuzmicki et al (13) in women with gestational diabetes. However, a study by Atégbo et al (9) revealed an increase in IL-10 levels in diabetic pregnant women. The literature reports that there is a greater IL-10 production in uncomplicated pregnancies as compared to those with pathologies such as spontaneous abortion and pre-eclampsia (14-16), thus supporting the role played by IL-10 in the maintenance of normal pregnancy.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Wood et al 16 have reported diminished expression of IL-4 in thymocytes of diabetic mice. Moreover, we have previously shown in clinical and experimental studies that a decrease of IL-4 may favour the onset of diabetic pregnancy in humans 9 and animals 10,11 . Type 2 diabetes has also been revealed as a chronic inflammatory disease promoted by changes in immune cell function and several studies have indicated that T cells are important mediators of inflammation in this disease 18,19,24,25 .…”
Section: Discussionmentioning
confidence: 95%
“…These cytokines act on liver, adipose tissue, brain, and pancreatic β-cells leading to a disrupted lipid metabolism which is the main risk factor for atherosclerosis, obesity and insulin resistance associated with type 2 diabetes 7,8 . We have previously demonstrated, in human and animal studies, the implication of T-cell differentiation through Th1/ Th2 cytokines in the modulation of gestational diabetes and macrosomia [9][10][11][12][13] . Nowadays, it is well known that naïve Th0 cell can differentiate into specific Th subsets (Th1, Th2, Th9, Th17, Th22, Treg,…) under the influence of cytokines, which on one hand can promote differentiation into a specific subset or on the other hand block differentiation towards a functionally-opposing subset 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos clínicos têm mostrado que, quando comparados com os valores normais, as mães DMG assim como as mães controle exibiram hipertrigliceridemia e hipercolesterolemia durante a gravidez e não houve diferença significativa entre mulheres saudáveis e diabéticas (45)(46)(47). No entanto, os bebês macrossômi-cos mostraram altos níveis de triglicerídeos e colesterol sérico total e livre em comparação aos bebês controle (46,47). O diabetes experimental também tem sido prejudicial ao metabolismo lipídico materno e fetal.…”
Section: Distúrbios Metabólicosunclassified